Internet multimedia computing and service : 9th International Conference, ICIMCS 2017, Qingdao, China, August 23-25, 2017, Revised selected papers /: 9th International Conference, ICIMCS 2017, Qingdao, China, August 23-25, 2017, Revised selected papers. (2018) - Unknown
No abstract available